Economic governance: Improving the economic and regulatory environment for supporting private sector activity - Colin Kirkpatrick (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper reviews the state of knowledge on the effectiveness of donor interventions aimed at improving the regulatory environment for private sector development in developing countries. Where regulatory reform is undertaken, the expectation is that there will be improvements to economic and welfare outcomes. By providing a review of the evidence on the results of regulatory reform, the paper aims to increase understanding of the types of interventions that are likely to have a positive impact on private sector development in developing countries.
Keywords: L51; O19; 330; economic regulation; regulatory reform; impact evaluation; private sector development; Privatwirtschaft; Regulierung; Entwicklungsländer